(untitled) (Homoeopathy for All, 2026)
Food allergy is an increasingly prevalent immunological disorder, particularly affecting children and young adults, where the burden is both clinically significant and rising. Recent epidemiological data indicate that food allergy affects approximately 6–8% of children under 5 years and nearly 4–5% of older children and adolescents, with persistence into adulthood observed in a substantial proportion of cases. In young adults, prevalence estimates range between 3–4%, often representing either persistent childhood allergies or newly developed sensitivities. Notably, studies suggest that over the past two decades, there has been a two- to three-fold increase in pediatric food allergy cases globally, with similar upward trends reported in urban populations and developing countries, including India. This rise has been attributed to factors such as altered dietary habits, reduced microbial exposure (hygiene hypothesis), environmental pollution, and early-life gut microbiome disturbances. At the mechanistic level, food allergy is primarily associated with the loss of oral tolerance a highly regulated immunological process by which the gastrointestinal immune system learns to recognize and remain unresponsive to harmless food proteins. This tolerance is mediated by complex interactions involving gut-associated lymphoid tissue (GALT), antigen-presenting cells, and regulatory T cells (Tregs), which actively suppress hypersensitivity reactions. Such intolerances have been observed with foods containing soy, gluten, nuts, and others.